Effective writing in English
385 p. 1 illus.
Keywords: We learn to speak and understand our native language without any great effort, for these are natural aspects of the maturation of every human being. The skills of reading and writing, by contrast, have to be learned, usually in an educational context. Now, when it comes to a foreign language, all the skills (speaking, un derstanding, reading and writing) have to be learned - nothing can be acquired without considerable effort. This learning process does not take place in a vac uum: it is heavily influenced by our previous experience of acquiring our native language and learning to read and write it. These facts have been taken as the background to this book. We aim this book at native speakers of Dutch who have learned to read and write their own language, and who now wish to add skill in writing English to their repertoire. Since this is our well-defined target group, we will be continually pointing to those aspects of written English which differ from comparable aspects of written Dutch, while also giving a complete guide to the writing process. There are two matters concerning the presentation of information in this book that require clarification in advance. Firstly, the book contains hundreds of numbered examples.